ESI‐QTof‐MS characterization of hirsutinolide and glaucolide sesquiterpene lactones: Fragmentation mechanisms and differentiation based on Na+/H+ adducts interactions in complex mixture. (17th December 2019) - da Silva, Layzon A.L.; Sandjo, Louis P.; Misturini, Alechania; Caramori, Giovanni F.; Biavatti, Maique W.
Abstract: Sesquiterpene lactones (SL) have been reported with various biological effects. Among the described SL skeletons, hirsutinolide and glaucolide have not been extensively studied by mass spectrometry (MS), especially how to distinguish them in organic matrices. Thus, this paper reports (1) a strategy of their differentiation based on MS behavior during the ionization and (2) a proposal of the fragmentation pattern for both SL‐subtypes. ESI(+)‐HRMS data of four isolated SL (hirsutinolides 1 and 3 ; glaucolides 2 and 4 ) were recorded by direct and UPLC water‐sample combined injections. These analyses revealed that hirsutinolides and glaucolides formed [M+Na] + ion during the operation of the direct MS injection, and ([M+Na] + and [M+H‐H2 O] + ) and [M+H] + ions were respectively observed for hirsutinolides and glaucolides during the operation of combined UPLC water and sample MS injection. Computational simulations showed that the complex hirsutinolide (1 )‐Na + formed with a lower preparation energy compared with the complex glaucolide (2 )‐Na + . However, despite their different behavior during the ionization process, ESI(+)‐HRMS/MS analyses of 1 ‐4 gave similar fragmentation patterns at m/z 277, 259, 241, and 231 that can be used as diagnostic ions for both skeletons. Moreover, the differentiation strategy based on the nature of the complex SL‐adducts and their MS/MS fragmentation pattern were successfully applied for the chemical characterization of the extract from Vernonanthura tweedieana using UPLC‐ESI‐HRMS/MS. Among the characterized metabolites, SL with hirsutinolide and glaucolide skeletons showed the aforementioned diagnostic fragments and an ionization behavior that was similar to those observed during the water‐sample combined injection.